Neurolaryngology (Springer International Publishing, 2018)
This book, endorsed by the European Laryngological Society, is a comprehensive guide to key topics in neurolaryngology, which enables readers to quickly identify and implement solutions in concrete situations likely to arise in everyday clinical practice. It includes detailed information on conditions such as vocal cord paresis/paralysis, laryngeal dystonia, and upper motor neuron disorders and offers clear advice on imaging and assessment, highlighting the role and performance of electromyography. Treatment options are extensively described, and there are individual chapters on functional therapy, botulinum toxin injection, the full range of phonosurgery options (including transoral endoscopic techniques, office-based phonosurgery, framework surgery, and laryngeal reinnervation), and laryngeal transplantation. With numerous accompanying videos, the book is a valuable resource for otorhinolaryngologists, speech pathologists and neurologists. .